Disbursement Process of FDSE Funds and its influence on Student Retention: A case of Migori County, Kenya - Achieng, Madeleine Sophie Barat; Elizabeth Nduku; Harriet Njui (IJRDO- Journal of Educational Research, 2021)
Public provision of educational services in “Sub-Saharan Africa” according to UNESCO (2011) is constrained by unavailability of public resources. Reviewed literature clearly indicate that delays in disbursement of free day secondary education funds have indeed affected the smooth running of public secondary schools especially in West and East African regions. For example a study by Koramoah (2016) on financing secondary education in Ghana confirmed that despite the strong political commitment to redress historical inequities in educational funding mechanisms and policy actions in relation to education, financing of secondary education appear to fall short of achieving the desirable goals. Koramoah (2016) also found that there were weak internal controls and monitoring systems and that the government’s inability to release funds on time led to delays of the government subsidy. Studies done in Kenya by Mueni, Kimiti and Mulwa (2019) and Koskei (2017) point to the same problem and this makes the current study in Migori County, a different geographical location, timely and relevant. The study was anchored on retention theory and targeted 215 public day schools. The actual sample was made of 19 schools, 19 school principals, 76 class teachers, 228 students, 31 parents and 1 Quality Assurance and Standards Officer. The study adopted a convergent parallel mixed method design using a cross sectional survey design for the quantitative method and a case study design for the qualitative method. Data were collected using questionnaires, interview guides, document analysis guide and focus group discussions. Descriptive and inferential statistics were generated using MS Excel 2018 and SPSS version 21. Qualitative data from the interviews and focus group discussions were analyzed thematically and report given in narrative form and direct quotes. The findings revealed that there are delays in the flow of FDSE funds from the Treasury and that late registration and not having accurate details of students in the NEMIS portal also affect the amounts sent to schools. The study recommended that the MoES&T should be prompt in releasing funds at the beginning of each term so that school programmes and budgets are not interfered with. The MoES&T needs to be consistent in evaluating the effectiveness and efficiency of the FDSE disbursement process.